Understanding of relationship between dopant and substitutional site to develop novel phase-change materials based on In3SbTe2 - Choi, Minho; Choi, Heechae; Ahn, Jinho; Kim, Yong Tae (IOP PUBLISHING LTD, 2019)
For over a decade, phase-change materials have been widely researched using various materials and methods. Despite efforts, the design of novel materials is nowhere near reported. In this paper, we provide the data for doping in In3SbTe2 material with doping formation energy and distortion angle at In, Sb, and Te sites. Information on the 29 dopants reduces unnecessary time cost to select the dopant for the lST material since the dopant with the positive and big formation energy should be excluded. In addition, excessive dopants disturb the stable phase transition, for this reason, the approximate limit of concentration for doping is suggested with experimental results through XRD, TEM, and electrical characteristics. This study gives one guideline of the many methods to develop and discover the novel materials in terms of substitutional site and the amount of dopant. (C) 2019 The Japan Society of Applied Physics
Keywords: GENERALIZED GRADIENT APPROXIMATION; CRYSTALLIZATION; DYNAMICS; GROWTH